(untitled) (Indian Journal of Nematology, 2025)
A field experiment was conducted to study the effect of soil solarization on rice root-knot nematode, Meloidogyne graminicola in rice during kharif seasons, 2016–2020. The experiment was laid out in a paired plot with two treatments viz., soil solarization of the nursery beds area after applying light irrigation covered with 25 μm transparent polythene sheet for 15 days during months of May-June followed by carbofuran 3G as soil application @ 1 kg a.i./ha at 45 days after transplanting (DAT), and untreated check during the first two years i.e., 2016 and 2017. Results revealed that soil solarization in combination with carbofuran significantly reduced the final nematode population (84.3%) and increased the yield to an extent of 13.8 per cent over untreated check. During 2018–2020, treatments were - soil solarization of the nursery beds area after applying light irrigation covered with 25 μm transparent polythene sheet for 15 days during the months of May-June, and untreated check. Soil solarization in the nursery area significantly reduced the final nematode population (62.6%) and increased the yield by 17.2 per cent over the untreated check. It was also observed that a transparent polythene sheet raises the soil temperature by 7°C and reaches up to 40–49°C in the upper 15 cm of soil profile.